Debt Policy Study with Economic and Non-Economic Approach (A Modigliani Miller Theory Testing with Mixed Method Approach) - Pradika, Novaldy Arief (Devotion : Journal of Research and Community Service, 2025)
This research aims to test debt policy with economic and non-economic approaches and to test the Modigliani-Miller theory. This research uses a mixed method approach by first conducting interviews to obtain qualitative data, followed by quantitative data collection through surveys. The data are then analyzed using descriptive techniques and presented in tables to describe data on Debt Policy Studies with Economic and Non-Economic Approaches. The findings show that debt (UT) has a significant negative influence on the prosperity of the company (MK), indicated by a negative coefficient value. This aligns with the opinion of Modigliani and Miller (MM), who argue that companies can increase their value if they use as much debt as possible (in a tax situation), although this view invites criticism and objections from practitioners. However, one of these objections arises from the assumptions used by MM in their analysis. This demonstrates that the company must consider how to repay the debt, which is consistent with the Qur'an, Surah An-Nisa, verse 29, and highlights that debt has a significant effect on the company's profit. In line with this conclusion—that debt negatively influences the prosperity of the company, while also affecting the company's profit—it is expected that entrepreneurs continuously monitor and evaluate their business activities, particularly the way company management handles debt control.